Design and Construction of a Pneumatic Vibratory Conveyer. - Kalagala, Abdulbast (Kabale University, 2024)
Tea, an aromatic beverage, is made by steeping hot water over cured or fresh leaves of Camellia taliensis. Typical tea processing stages include withering, rolling, oxidation, sieving, and firing. This project focused on designing a pneumatic-powered vibratory conveyor specifically for sieving tea leaves at the Kigezi Highland Tea Factory, Kabale branch. Vibratory conveyors are durable systems used to transport or sieve materials ranging from fine to coarse grains in workshops or factories. The project aimed to create a pneumatic-powered vibratory conveyor for industrial settings, offering lower power input and higher load capacity than traditional electric vibratory conveyors. At Kigezi Highland Tea Factory, the existing electric conveyor faces challenges, such as limited load capacity and high power consumption, which this design addresses. The new conveyor is designed to handle up to 25 kg, significantly more than the current 6 kg limit, and reduces energy consumption through pneumatic power. The system features a motor-driven single-stage compressor that supplies compressed air to two vibrators on the conveyor trough, enabling material transport and sieving. Designed for transferring and sieving tea leaves, the conveyor’s large trough surface allows for increased load capacity and enhanced sieving efficiency. Design methods included AutoCAD for 2D illustrations and sizing, MATLAB for calculations and vibration analysis, SOLIDWORKS for 3D modeling of the trough, frame, and components, and ANSYS for system analysis.